Not All Executive Functions Are Related to Intelligence - Friedman, Naomi P.; Miyake, Akira; Corley, Robin P.; Young, Susan E.; DeFries, John C.; Hewitt, John K. (Psychological Science, 2006)
Accumulating evidence suggests that executive functions (EFs) are related to intelligence, despite neuropsychological results initially considered evidence of no such relation. However, findings that EFs are not unitary raise the issue of how intelligence relates to different EFs. This study examined the relations of fluid and crystallized intelligence and Wechsler Adult Intelligence Scale IQ to three separable EFs—inhibiting prepotent responses (inhibiting), shifting mental sets (shifting), and updating working memory (updating)—in young adults. Updating was highly correlated with the intelligence measures, but inhibiting and shifting were not. Furthermore, in structural equation models controlling for the inter-EF correlations, updating remained strongly related to intelligence, but the relations of inhibiting and shifting to intelligence were small and not significant. The results indicate that intelligence measures differentially relate to these three EFs, suggesting that current intelligence measures do not equally assess a wide range of executive control abilities likely required for many “intelligent” behaviors.